A real-time line segmentation algorithm for an offline overlapped handwritten Jawi character recognition chip - Razak Z.; Zulkiflee K.; Salleh R.; Yaacob M.H.; Tamil E.M. (Faculty of Computer Science and Information Technology, 2023)
Overlapped characters between upper and lower lines can cause a major problem in line segmentation of cursive characters such as Jawi (similar to Arabic characters). In this paper we will discuss our fast approach using a tangent value to find a separation point (SP) for accurate line segmentation without data loss. This approach will be used to design a dedicated Jawi Character Recognition Chip with the objective of obtaining 90% recognition accuracy.